Urgensi Supervisi Klinis dalam Penerapan Kurikulum Merdeka di Daerah 3T - Nadia, Deni Okta; Indriani, Elfi; Yulia, Rahmi; Marsidin, Sufyarma (MODELING: Jurnal Program Studi PGMI, 2023)
Freedom of learning issued by the government has not fully paid attention to the 3T (Foremost, Outermost and Disadvantaged) regions. The 3T area needs professional teachers who have the ability and understand the main tasks and functions as teachers and can make innovations so that the learning process at school is fun for students. Clinical supervision needs to be carried out by school principals in order to help teachers overcome problems faced by teachers in learning, especially in the 3T areas. In this study, a qualitative approach research method was used with data collection techniques in the form of case studies from research journals, books and related articles. The results of the analysis show that the successful implementation of clinical supervision is characterized by an increase in the teacher's ability to plan, implement, and evaluate the learning process, the quality of learning carried out by the teacher becomes better. The main problem of the clinical supervision process in the 3T area is difficult access resulting in the supervision process not going well. In addition, there are other factors that influence teacher competency improvement, namely individual factors and organizational environmental factors.